Strategi Peningkatan Peringkat Perguruan Tinggi Versi Kemristekdikti (Studi pada Universitas Brawijaya) - Mochammad Rozikin; Maya Kurniawati; Khairunnisa Aliyyah (Kelola: Jurnal Manajemen Pendidikan, 2020)
The Ministry of Research, Technology and Higher Education has announced the results of ranking universities in Indonesia. Universitas Brawijaya has experienced ups and downs in ranking. During the period of 2015-2019, the best ranking of Universitas Brawijaya in the fifth recruitment in 2016. This study aims to formulate a series of optimization strategies for improving UB's rank. Research approach with qualitative methods and the literature review technique and focusing on several approaches to formulate strategy, which are Balanced Scorecard, SWOT, and SPACE. Retrieval of data with the method of observation and documentation. While data validation with Triangulation. The results of this study explained that the Balanced Scorecard, SWOT, and SPACE could be used to solve strategy formulation problems. There are eleven strategic steps to optimize and improve Universitas Brawijaya's ranking by following the indicators set by the Ministry of Research, Technology and Higher Education.